2022
DOI: 10.3390/jcm11164661
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Nootropics in Combination with Cholinesterase Inhibitors on Cognitive Function in Mild-to-Moderate Dementia: A Study Using Real-World Data

Abstract: The clinical benefits of nootropics in the treatment of cognitive decline has been either limited or controversial. This study aimed to observe the effectiveness of cholinesterase inhibitor (ChEI) and nootropics combination in the treatment of cognitive impairment in dementia. Data were based on electronic medical records in a university health system. Patients with mild-to-moderate dementia and no history of prior cognitive enhancer use were included (n = 583). The subjects were categorized into the ChEI only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
2
0
2
Order By: Relevance
“…GPC enhances memory and cognitive function and is well-known to be effective in the treatment of several neurodegenerative and vascular diseases such as Alzheimer’s disease and dementia ( 21 23 ). GPC has been shown to be more effective when combined with cholinesterase inhibitors ( 24 , 25 ). Numerous studies have identified the favorable effects of GPC in the treatment of the sequelae of cerebrovascular accidents ( 26 28 ).…”
Section: Choline Alfosceratementioning
confidence: 99%
See 1 more Smart Citation
“…GPC enhances memory and cognitive function and is well-known to be effective in the treatment of several neurodegenerative and vascular diseases such as Alzheimer’s disease and dementia ( 21 23 ). GPC has been shown to be more effective when combined with cholinesterase inhibitors ( 24 , 25 ). Numerous studies have identified the favorable effects of GPC in the treatment of the sequelae of cerebrovascular accidents ( 26 28 ).…”
Section: Choline Alfosceratementioning
confidence: 99%
“…GPC has been shown to exhibit a favorable action in experimental models of the aging brain as well as in a rat model of pilocarpine-induced seizure ( 29 , 30 ), and to promote neuronal differentiation in a rat model of noise-restraint stress ( 29 ). In vitro assays performed in the SH-SY5Y human cell line have revealed that this cholinergic compound antagonizes neurotoxicity triggered by the fragment Aβ ( 25 35 ) of the Alzheimer’s amyloid β-peptide and attenuates the Aβ-induced phosphorylation of the Tau protein ( 31 ), by sustaining the expression level of synaptic vesicle proteins, such as synaptophysin ( 32 34 ). GPC was also shown to increase hippocampal neurogenesis, providing protection against seizure-induced neuronal death and cognitive impairment ( 26 ) and to antagonize scopolamine-induced amnesia enhancing hippocampal cholinergic transmission, suggesting that the behavioral effects of GPC could be related to its property to increase hippocampal synthesis and release of ACh ( 35 – 38 ).…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Во многих зарубежных и отечественных рандомизированных плацебо-контролируемых исследованиях показано положительное влияние холина альфосцерата (Церетон®) на КФ как на стадии недементных (легких и умеренных) КР, так и на стадии деменции при сосудистых нарушениях (хронической ишемии и инсульте) и БА [18][19][20][21][22][23].…”
unclassified
“…Препарат хорошо себя зарекомендовал и при лечении деменции. В многоцентровом рандомизированном клиническом исследовании ASCOMALVA терапии пациентов с БА на стадии легкой или умеренной деменции препаратом холина альфосцерат, применяемым в дозировке 1200 мг/сут на протяжении 180 сут, показано значимое улучшение когнитивного статуса по всем психометрическим шкалам при его добавлении к ингибиторам ацетилхолинэстеразы [21][22][23]. Препарат хорошо переносился и практически не вызывал побочных эффектов.…”
unclassified